Akuntabilitas Keuangan dan Kompetensi Aparatur Sipil Negera Terhadap Akuntabilitas Kinerja Dinas Perdagangan Perindustrian Kota Pekanbaru - Fachroh Fiddin; Erma Domos (Journal of Business and Economics Research (JBE), 2020)
This study aims to analyze and examine the effect of the application of financial accountability and employee competence to the performance accountability of government agencies in the Department of Trade and Industry of Pekanbaru City. Research respondents from this study are all civil servants at the Department of Trade and Industry of the City of Pekanbaru. The data used in this study were obtained from individual perceptions regarding the application of financial accountability, employee competence and accountability of government agencies' performance in the Pekanbaru City Department of Trade and Industry. Data obtained after distributing questionnaires were 81 people. Data analysis uses multiple regression techniques that are supported by the data brother. The results showed that the application of financial accountability did not affect the accountability of the performance of government agencies and the competence of employees both simultaneously and partially affected the performance accountability of government agencies